2021
DOI: 10.3390/f12040397
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Unmanned Aerial Vehicles Forest Remote Sensing—A Systematic Review. Part II: Research Applications

Abstract: Forest sustainable management aims to maintain the income of woody goods for companies, together with preserving non-productive functions as a benefit for the community. Due to the progress in platforms and sensors and the opening of the dedicated market, unmanned aerial vehicle–remote sensing (UAV–RS) is improving its key role in the forestry sector as a tool for sustainable management. The use of UAV (Unmanned Aerial Vehicle) in precision forestry has exponentially increased in recent years, as demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 275 publications
2
50
0
1
Order By: Relevance
“…Although LiDAR could measure the riparian forest dendrometric features accurately, this technology is quite expensive. The authors of [90] reported a major drawback in comparison to LiDAR and photogrammetry, where the latter is limited to the characterization of the outer canopy envelope, while LiDAR can acquire the vertical profile of vegetation also operating in under-canopy conditions. Regarding the costs, [91] estimated a total cost, including field crew, of about 9300 € for UAV-LiDAR and 6800 € for UAV-SfM to measure vegetation height for 30 sites on seismic lines.…”
Section: Discussionmentioning
confidence: 99%
“…Although LiDAR could measure the riparian forest dendrometric features accurately, this technology is quite expensive. The authors of [90] reported a major drawback in comparison to LiDAR and photogrammetry, where the latter is limited to the characterization of the outer canopy envelope, while LiDAR can acquire the vertical profile of vegetation also operating in under-canopy conditions. Regarding the costs, [91] estimated a total cost, including field crew, of about 9300 € for UAV-LiDAR and 6800 € for UAV-SfM to measure vegetation height for 30 sites on seismic lines.…”
Section: Discussionmentioning
confidence: 99%
“…Along with this, satellite data can also help with site analysis and selection. For instance, they can be utilized for determining fire perimeters and/or classes/severity of forest loss (by analyzing pre-and post-fire scenarios), and this can be incorporated as a parameter while selecting flight paths, dispersal intensities and seed types [74,75]. Moreover, in several cases, when partial cover image acquisitions occur (due to low lighting, wind speed, etc.)…”
Section: Forest Regeneration With Unmanned Aerial Vehicle-supported Seed Sowing (Uavsss)mentioning
confidence: 99%
“…Traditional remote sensing uses satellite imagery and it has improved in terms of the type of sensors, spatial and temporal resolution (Chavana-Bryant et al, 2019;Lechner et al, 2020). UAVs provide relevant canopy information at flexible times, with a higher spatial resolution and a relatively cheaper price when compared to satellite data (Lechner et al, 2020;Dainelli et al, 2021). Arboreal camera traps are effective at capturing photos of canopy vertebrates if foliage is removed from the immediate vicinity of the camera to prevent false triggering (Di Cerbo and Biancardi, 2013;Gregory et al, 2014;Whitworth et al, 2016;Bowler et al, 2017;Nazir and Kaleem, 2021).…”
Section: Modes Of Access and Experimental Designmentioning
confidence: 99%
“…The combination of machine learning techniques with remote sensing data allows several canopy studies ranging from semi and automatic identification and quantification of canopy species using conventional RGB cameras (Tagle Casapia et al, 2019;Ferreira et al, 2020;Wang et al, 2021), multispectral cameras (Gini et al, 2014;Wagner et al, 2020) or hyperspectral sensors (Dalponte et al, 2014), to assess health status (Dainelli et al, 2021), phenology (Feng et al, 2021), above-ground biomass estimation/quantification using RGB, radar or Lidar (Marks et al, 2014;Brede et al, 2019;Dainelli et al, 2021), canopy traits (Thomson et al, 2018;Ganivet and Bloomberg, 2019), or to detect fauna with thermal sensors (Spaan et al, 2019;Zhang et al, 2020). In all the cases, to be most effective, calibration against carefully chosen samples at the top of the canopy is required to provide accurate results (Käslin et al, 2018;Chavana-Bryant et al, 2019;Schweiger et al, 2020).…”
Section: Modes Of Access and Experimental Designmentioning
confidence: 99%